Foreign Language Learning Practices and Attitudes among Ukrainian University Students - Khalymon, Iryna; Larina, Tetiana; Smelianska, Viktoriia (Pedagogical Discourse, 2025)
This research investigates foreign language learning among tertiary students in Ukraine, emphasizing its relevance to improving language education in diverse contexts. The study aimed to identify key factors influencing students’ foreign language learning outcomes and practices. A specially designed questionnaire was administered to 643 students at Nizhyn Mykola Gogol State University, focusing on their attitudes, motivation, perceived necessity of foreign languages for future goals, and learning practices. The research employed a quantitative methodology, using descriptive and inferential statistics. Data analysis included correlation and regression analyses to determine predictors of foreign language learning success. The findings indicate that the majority of respondents perceive their foreign language knowledge as satisfactory or poor. Despite this, students generally exhibit a positive attitude toward foreign language learning, with many expressing a desire to improve and recognizing the importance of foreign languages for their future. Results revealed that the students’ positive attitudes toward foreign language learning are driven by the instrumental form of extrinsic motivation, which align foreign language learning with career and educational aspirations. However, a notable gap between positive attitudes and actual learning practices emerged, as only a small proportion of participants consistently dedicated time to improving their foreign language skills. The analyses highlighted satisfaction with foreign language knowledge, engagement in foreign language practice, and positive attitudes toward foreign languages as compulsory subjects as significant predictors of success. In contrast, factors such as gender, year of study, and perceived necessity of foreign languages for daily use or further education did not significantly impact outcomes. The study underscores the importance of aligning foreign language instruction with students’ real-world aspirations to sustain motivation and improve outcomes. Additionally, findings emphasize the value of personalized and interactive learning experiences, suggesting adjustments to curricula and educational policies to better meet learners’ needs.